Dbx1-expressing cells are necessary for the survival of the mammalian anterior neural and craniofacial structures. - Frédéric Causeret; Monica Ensini; Anne Teissier; Nicoletta Kessaris; William D Richardson; Thibaut Lucas de Couville; Alessandra Pierani (PLoS ONE)
Development of the vertebrate forebrain and craniofacial structures are intimately linked processes, the coordinated growth of these tissues being required to ensure normal head formation. In this study, we identify five small subsets of progenitors expressing the transcription factor dbx1 in the cephalic region of developing mouse embryos at E8.5. Using genetic tracing we show that dbx1-expressing cells and their progeny have a modest contribution to the forebrain and face tissues. However, their genetic ablation triggers extensive and non cell-autonomous apoptosis as well as a decrease in proliferation in surrounding tissues, resulting in the progressive loss of most of the forebrain and frontonasal structures. Targeted ablation of the different subsets reveals that the very first dbx1-expressing progenitors are critically required for the survival of anterior neural tissues, the production and/or migration of cephalic neural crest cells and, ultimately, forebrain formation. In addition, we find that the other subsets, generated at slightly later stages, each play a specific function during head development and that their coordinated activity is required for accurate craniofacial morphogenesis. Our results demonstrate that dbx1-expressing cells have a unique function during head development, notably by controlling cell survival in a non cell-autonomous manner.